THE EFFICIENCY OF SMALL-SCALE INSTRUCTION STRATEGIES IN INITIATIVES DESIGNED TO EDUCATE ENGLISH-SPEAKING TEACHERS - Nayeem, Mohammad Abu (CALL, 2025)
This study explores the pedagogical impact of small-scale instruction strategies, also known as microteaching, on the professional development of English-speaking educators. In response to the persistent theory-practice divide in teacher education, small-scale instruction offers a practical framework for skill-based learning through iterative teaching sessions, guided feedback, and reflective practices. This research investigates how microteaching enhances classroom performance, instructional confidence, and student-centered delivery. The study applies a qualitative, literature-based method and synthesizes findings from over 80 global and regional peer-reviewed sources. Key challenges identified include inadequate theoretical integration, insufficient instructional resources, limited digital infrastructure, and evaluation gaps. At the same time, the literature highlights the potential of video-based feedback, context-sensitive teaching simulations, and constructivist alignment to optimize learning outcomes. The findings advocate for a comprehensive, digitally supported, and culturally responsive microteaching framework, particularly suited for low-resource and linguistically diverse educational contexts. This paper contributes to teacher training discourse by offering scalable, evidence-based models adaptable to dynamic classroom environments.